ANALISIS DAYA SAING USAHA PEMBESARAN IKAN NILA PETANI PEMODAL KECIL DI KABUPATEN MUSI RAWAS - Ningsih, Very Yarda; Asriani, Putri Suci; Sriyoto, Sriyoto (Jurnal AGRISEP, 2016)
This research was done to investigate whether tilapia growers has business competitiveness both in competitive and comparative. This study aimed to analyze the competitive advantage, comparative advantage, the impact of government policies on output and input. Effect of output and input changing based on a sensitivity analysis on the competitiveness of tilapia fish rearing business, the level of tilapia grower business competitiveness between small farmers in Musi Rawas regency. The respondent was determined by purposive method deliberately carried out in accordance with the criteria set by the researcher. The respondents was conducted by using proportionate stratified random sampling. This study used the primary data and secondary data. The result of Pam Method shows that a small farmers of tilapia enlargement at musi rawas regency has competitive advantage with PCR < 1 by 0,55.  It also has comparativeadvantage with DRCR < 0,37.  The goverment policies toward  tradadable input produkction were in the form of subsidies.  Based of sensitivity analysis the enlargemen of tilapia will be lost if tilapia production decrease 10%, the price of tilapia it self decrease 5,5% and if the feed price increase 7%.